Sociodemographic and Pathological Study of Sudden Death Among Neonates and Infants: An Autopsy Based Study (Medico Legal Update, 2024)
Children dying within the first year of life is referred to as infant mortality and is an important key indicator for a country’s health and standard of living.  Every year, there is an estimated 4.5 million infant deaths around the world, accounting for almost 75% of deaths in children younger than 5 years. The studies based on infant deaths are relatively less in number worldwide.This study investigates the sociodemographic and pathological aspects of infant deaths through autopsy data.The objective of the study was to evaluate the pathology and causes of infant/neonatal deaths and analyze related social and demographic factors.A cross-sectional descriptive autopsy study was conducted at the Government Medical College, Kozhikode, covering 66 medicolegal infant death cases from April 2018 to October 2022. Data were collected via questionnaires and analyzed using SPSS software.Respiratory infections (37.14%) were the leading cause of infant deaths, while perinatal complications and congenital abnormalities each accounted for 25% of neonatal deaths. Most deaths occurred in the postneonatal period (77.1%), predominantly among male infants (63%) from rural areas (84.3%). Key findings included consolidation and bronchopneumonia in lung examinations.Significant associations were found with various factors, including the period of infancy, delivery type, co-sleeping history, and prior hospitalizations. Birth weight and histopathological lung findings were linked to sudden infant death syndrome (SIDS).